Observer-based volumetric flow control in nonlinear electro-pneumatic extrusion actuator with rheological dynamics - Chancharoen, Ratchatin; Sithiwichankit, Chaiwuth; Chaiprabha, Kantawatchr; Suthithanakom, Setthibhak; Phanomchoeng, Gridsada (Actuators, 2025)
Consistent volumetric flow control is essential in extrusion-based additive manufacturing, particularly when printing viscoelastic materials with complex rheological properties. This study proposes a control framework incorporating simplified rheological dynamics via a Kelvin-Voigt model that integrates nonlinear dynamic modeling, an unknown input observer (UIO), and a closed-loop PID controller to regulate material flow in a motorized electro-pneumatic extrusion system. A comprehensive state-space model is developed, capturing both mechanical and rheological dynamics. The UIO estimates unmeasurable internal states - specifically, syringe plunger velocity - which are critical for real-time flow regulation. Simulation results validate the observer’s accuracy, while experimental trials with a curing silicone resin confirm that the system can achieve steady extrusion and maintain stable linewidth once transient disturbances settle. The proposed system leverages a dual-mode actuation mechanism - combining pneumatic buffering and motor-based adjustment - to achieve responsive and robust control. This architecture offers a compact, sensorless solution well-suited for high-precision applications in bioprinting, electronics, and soft robotics, and provides a foundation for intelligent flow regulation under dynamic material behaviors.
Veröffentlicht: 14. Oktober 2025
Gesehen am 03.12.2025